Different roles of the small GTPases Rac1, Cdc42, and RhoG in CALEB/NGC‐induced dendritic tree complexity. Issue 1 (4th August 2016) - Schulz, Jana; Franke, Kristin; Frick, Manfred; Schumacher, Stefan
Abstract: Rho GTPases play prominent roles in the regulation of cytoskeletal reorganization. Many aspects have been elaborated concerning the individual functions of Rho GTPases in distinct signaling pathways leading to cytoskeletal rearrangements. However, major questions have yet to be answered regarding the integration and the signaling hierarchy of different Rho GTPases in regulating the cytoskeleton in fundamental physiological events like neuronal process differentiation. Here, we investigate the roles of the small GTPases Rac1, Cdc42, and RhoG in defining dendritic tree complexity stimulated by the transmembrane epidermal growth factor family member CALEB/NGC. Combining gain‐of‐function and loss‐of‐function analysis in primary hippocampal neurons, we find that Rac1 is essential for CALEB/NGC‐mediated dendritic branching. Cdc42 reduces the complexity of dendritic trees. Interestingly, we identify the palmitoylated isoform of Cdc42 to adversely affect dendritic outgrowth and dendritic branching, whereas the prenylated Cdc42 isoform does not. In contrast to Rac1, CALEB/NGC and Cdc42 are not directly interconnected in regulating dendritic tree complexity. Unlike Rac1, the Rac1‐related GTPase RhoG reduces the complexity of dendritic trees by acting upstream of CALEB/NGC. Mechanistically, CALEB/NGC activates Rac1, and RhoG reduces the amount of CALEB/NGC that is located at the right site for Rac1 activation at the cell membrane. Thus, Rac1, Cdc42, and RhoG perform very specific and non‐redundant functions at different levels of hierarchy in regulating dendritic tree complexity induced by CALEB/NGC. Rho GTPases play a prominent role in dendritic branching. CALEB/NGC is a transmembrane member of the epidermal growth factor (EGF) family that mediates dendritic branching, dependent on Rac1. CALEB/NGC stimulates Rac1 activity. RhoG inhibits CALEB/NGC‐mediated dendritic branching by decreasing the amount of CALEB/NGC at the plasma membrane. Palmitoylated, but not prenylated form of the GTPase Cdc42 decreases dendritic branching. CALEB/NGC and Cdc42 are not directly interconnected in regulating dendritic branching. Thus, CALEB/NGC organizes a Rho GTPase signaling module at the plasma membrane for shaping dendritic trees. Abstract : Rho GTPases play a prominent role in dendritic branching. CALEB/NGC is a transmembrane member of the epidermal growth factor (EGF) family that mediates dendritic branching, dependent on Rac1. CALEB/NGC stimulates Rac1 activity. RhoG inhibits CALEB/NGC‐mediated dendritic branching by decreasing the amount of CALEB/NGC at the plasma membrane. Palmitoylated, but not prenylated form of the GTPase Cdc42 decreases dendritic branching. CALEB/NGC and Cdc42 are not directly interconnected in regulating dendritic branching. Thus, CALEB/NGC organizes a Rho GTPase signaling module at the plasma membrane for shaping dendritic trees.